Analysis of Athlete Endurance: A Study on Female Volleyball Athletes - Yolanda Yolanda; Mimi Haetami; Novi Yanti; Athraa Abdulelah Abdulsatar; Musab Mohammed Abdullah (Khatulistwa Education Center, 2025)
Background. Endurance plays a crucial role in determining an athlete’s performance, especially in high-intensity sports such as volleyball, which requires repeated bursts of activity, rapid directional changes, and sustained physical effort. VO2max, an indicator of aerobic capacity, is a key factor influencing endurance levels. However, many volleyball clubs lack structured monitoring and training programs to optimize VO2max development.Objectives. This study aims to analyze the VO2max endurance levels of female volleyball athletes from the Nomen Nascio and Brojomusti clubs in Pontianak.Methods. A quantitative research approach was employed, utilizing a survey method with Yo-Yo Intermittent Recovery Test Level 1 as the primary instrument for measuring VO2max. The study involved 55 female volleyball athletes, consisting of 40 athletes from Nomen Nascio and 15 from Brojomusti. Data were analyzed using descriptive statistics to interpret the VO2max levels among participants.Results. The results indicated that 57.5% of Nomen Nascio athletes fell into the poor category, while only 10% were classified as good. In contrast, the Brojomusti club exhibited better endurance levels, with 40% categorized as good and 6.7% as excellent. The findings emphasize the need for targeted endurance training programs to improve VO2max, particularly for clubs with lower endurance levels.Conclusion. Coaches and sports practitioners can utilize these insights to design structured, sport-specific training regimens that enhance overall athletic performance and long-term player development. This study contributes to the field of sports science by providing empirical evidence on the endurance levels of female volleyball athletes and highlighting the disparities in VO2max between different clubs.